2014
DOI: 10.1002/cm.21178
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of the filament stabilizing versus destabilizing activities of cofilin through its secondary binding site on actin

Abstract: Cofilin is a ubiquitous modulator of actin cytoskeleton dynamics that can both stabilize and destabilize actin filaments depending on its concentration and/or the presence of regulatory co-factors. Three charge-reversal mutants of yeast cofilin, located in cofilin’s filament-specific secondary binding site, were characterized in order to understand why disruption of this site leads to enhanced filament disassembly. Crystal structures of the mutants showed that the mutations specifically affect the secondary ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 86 publications
(190 reference statements)
1
20
0
Order By: Relevance
“…Recent biochemical, structural, and cell biological evidence has suggested that Aip1 may enhance severing by competing with Cof1 for its second binding site on F-actin, leading to filament destabilization. Indeed, in support of this model, mutants in cof1 that disrupt its second F-actin binding site were found to be hyperactive for filament severing ( Aggeli et al 2014 ).…”
Section: Mechanisms Of Actin Assembly and Turnovermentioning
confidence: 87%
“…Recent biochemical, structural, and cell biological evidence has suggested that Aip1 may enhance severing by competing with Cof1 for its second binding site on F-actin, leading to filament destabilization. Indeed, in support of this model, mutants in cof1 that disrupt its second F-actin binding site were found to be hyperactive for filament severing ( Aggeli et al 2014 ).…”
Section: Mechanisms Of Actin Assembly and Turnovermentioning
confidence: 87%
“…In addition, it is yet to be determined precisely how AIP1 binding to a Cofilin-decorated region of a filament triggers severing. This may involve AIP1 displacing one or more Cof1 molecules from a patch to generate a local discontinuity that destabilizes filaments 44 , or AIP1 displacing one of Cofilin's two binding interactions with F-actin 45 . Finally, it will be important to study if and how Cofilin, Coronin and AIP1 work alongside other actin disassembly factors, for example, Srv2/CAP, GMF and possibly Twinfilin 16 18 46 47 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to consider how sequence differences between Cof1, Cof2, and ADF account for the differences in their severing activities. Previous studies found that differences in the actin-binding residues of the three ADF/Cofilins map to the F-site [9], and a recent study on yeast Cof1 demonstrated that point mutations in its F-site drastically enhance severing activity [50]. …”
Section: Discussionmentioning
confidence: 99%